Embedding First Nations Knowledges, perspectives, and experiences in university criminology curricula in Australia and Aotearoa New Zealand: Findings from a transnational survey - Jessamy Gleeson; Mark Wood; Kate Hutton Burns; Samantha Keene; Rachel Loney-Howes (2025)
As many universities strive to decolonise their curricula, understanding how criminologists in Australia and Aotearoa New Zealand are incorporating First Nations Knowledges, perspectives and experiences becomes crucial. Drawing on a survey of 176 criminology educators working in these countries, this study examined how First Nations’ insights are embedded in their teaching. The findings indicate that educators across the two countries are embedding a variety of approaches within their curricula but there is still much work to do. Educators from Aotearoa New Zealand utilise more approaches in their teaching than their Australian counterparts, which may speak to the more advanced policy positions regarding embedment of First Nations perspectives. Sustainable, long-term approaches require a whole-of-university approach so that the practice of embedment reflects the policy and intentions.